Application and Evaluation of Case-Based Learning as a Part of Early Clinical Exposure for Undergraduate Medical Education Program - Daulatabad, Vandana; K., Prafull; Kadadi-Patil, Dr. Surekha S.; Patil, Ramesh S. (International Journal of Innovative Research in Medical Science, 2020)
Introduction: Medical Education is witnessing a significant transition and global shift towards competency based medical education (CBME) which includes early clinical exposure (ECE) program to help students apply and correlate principles of preclinical subjects with clinical scenarios, in various forms and in a variety of settings. One of the easy and feasible methods of ECE being Case Based Learning (CBL), our study aimed to design a case scenario and to evaluate impact of case base learning as a part of ECE module in first year undergraduate medical teaching program in nerve muscle physiology. Methods: The present study was conducted in 96 students at Ashwini Rural Medical College Hospital and Research Centre, Solapur after obtaining institutional ethics committee approval. 3 hrs session of CBL was conducted for a case scenario on myasthenia gravis in the nerve muscle physiology module. The students’ responses on pre-test, post-test and their insights regarding the CBL were taken through a pre validated questionnaire using 5-point Likert scale. Results: High impact of CBL was seen as significant improvement in student’s performance. Maximum students felt CBL to be easy method of learning and was highly appreciated through their feedback. Conclusion: CBL was found to have positive impact on understanding and perception of topic. CBL helped students to understand, evaluate, analyze, diagnose and interpret the case, paving them towards newer approach of self-directed and vertical integrated learning. CBL is easier, feasible an effective method among other early clinical exposure methods as it involves students in deeper and self-directed active learning, encouraging and promoting them to reach higher levels of cognitive domain of Bloom’s taxonomy. This method will be very useful in its practical implementation during online classes for ECE module in the threat of COVID 19 situation as well.